Image and audio fractal compression: comprehensive review, enhancements and research directions - Ahmed Huaasin Ali; Ali Nihad Abbas; Loay Edwar George; Mohd Rosmadi Mokhtar (Institute of Advanced Engineering and Science, 2019)
This study aims to review the recent techniques in digital multimedia compression with respect to fractal coding techniques. It covers the proposed fractal coding methods in audio and image domain and the techniques that were used for accelerating the encoding time process which is considered the main challenge in fractal compression. This study also presents the trends of the researcher's interests in applying fractal coding in image domain in comparison to the audio domain. This review opens directions for further researches in the area of fractal coding in audio compression and removes the obstacles that face its implementation in order to compare fractal audio with the renowned audio compression techniques.